Performance of Zika assays in the context of Toxoplasma gondii, parvovirus B19, rubella virus, and cytomegalovirus (TORCH) diagnostic assays - Voordouw, Bettie; Jänisch, Thomas (Clinical microbiology reviews, 2019)
Infections during pregnancy that may cause congenital abnormalities have been recognized for decades, but their diagnosis is challenging. This was again illustrated with the emergence of Zika virus (ZIKV), highlighting the inherent difficulties in estimating the extent of pre- and postnatal ZIKV complications because of the difficulties in establishing definitive diagnoses. We reviewed the epidemiology, infection kinetics, and diagnostic methods used for Toxoplasma gondii, parvovirus B19, rubella virus, and cytomegalovirus (TORCH) infections and compared the results with current knowledge of ZIKV diagnostic assays to provide a basis for the inclusion of ZIKV in the TORCH complex evaluations. Similarities between TORCH pathogens and ZIKV support inclusion of ZIKV as an emerging TORCH infection. Our review evaluates the diagnostic performance of various TORCH diagnostic assays for maternal screening, fetal screening, and neonatal screening. We show that the sensitivity, specificity, and positive and negative predictive value of TORCH complex pathogens are widely variable, stressing the importance of confirmatory testing and the need for novel techniques for earlier and accurate diagnosis of maternal and congenital infections. In this context it is also important to acknowledge different needs and access to care for different geographic and resource settings.
Published 11 December 2019
Gesehen am 21.04.2020